Self-Efficacy and Self-Adjustment of First-Year Students Living Away from Home: Implications for Educational Management - Rangga Febriano Wahyu Setiawan; Riza Noviana Khoirunnisa (Journal of Educational Management Research, 2026)
The transition from high school to university constitutes a critical socio-psychological phase, particularly for first-year students living away from home who must simultaneously manage independence and academic adaptation. This study aims to examine the relationship between self-efficacy and self-adjustment among first-year psychology students at Universitas Negeri Surabaya who have migrated from their home regions. Employing a quantitative correlational research design, the study involved 237 students selected through purposive sampling. Data were collected using the General Self-Efficacy Scale (GSES) and the Inventory of New College Student Adjustment (INCSA). The data were analyzed using Spearman’s rho correlation technique. The results revealed a strong and positive relationship between self-efficacy and self-adjustment (ρ = 0.701, p < 0.001), indicating that students with higher levels of self-efficacy tend to demonstrate better adjustment capabilities in academic, social, and emotional domains. These findings highlight self-efficacy as a crucial internal resource in coping with cultural shock, academic demands, and psychosocial challenges during the first year of university life. From an educational management perspective, the study implies the importance of integrating self-efficacy development strategies into student management systems, particularly through orientation programs, academic advising, and counseling services. Strengthening self-efficacy can support more effective student adjustment, retention, and overall academic success